2012
DOI: 10.1007/s10509-012-1059-9
|View full text |Cite
|
Sign up to set email alerts
|

More on modified Gauss-Bonnet gravity

Abstract: A model of modified gravity with non-minimal coupling between a general function of the Gauss-Bonnet invariant, f (G), and matter Lagrangian is an interesting proposal for description of early inflation and late-time cosmic acceleration. In the other hand, energy conditions are simple criteria for viability of a given gravity model. In this paper we consider the above mentioned model of modified gravity with f (G)-matter coupling and study it from the viewpoint of energy conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The model is based on a nonminimal coupling between a noncanonical scalar field (tachyon field) in the context of teleparallel gravity. It is shown in [39] that such a model presents phantom divide crossing during its evolution in agreement with cosmological observations. We have extracted the fixed points of the model and presented the conditions for their existence and stability.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…The model is based on a nonminimal coupling between a noncanonical scalar field (tachyon field) in the context of teleparallel gravity. It is shown in [39] that such a model presents phantom divide crossing during its evolution in agreement with cosmological observations. We have extracted the fixed points of the model and presented the conditions for their existence and stability.…”
Section: Resultssupporting
confidence: 77%
“…Tachyonic teleparallel dark energy has been studied in [39]. It is shown that such a scenario can realize phantom divide crossing during its evolution and so exhibits very interesting cosmological behavior.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to describe dark energy model, numerous studies have been performed in isotropic space-time such as scalar fields (quintessence, phantom, tachyon and etc.) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], modified gravity models [24][25][26][27][28][29][30][31], holographic models [32][33][34][35][36][37][38][39][40], interacting models [41][42][43][44][45][46][47][48][49][50][51][52], bouncing model [53][54][55...…”
Section: Introductionnmentioning
confidence: 99%